Finite Element simulation for three dimensional thermal analysis of Multi-Chip Module. (15th April 2009) - Ping, Yang; Qin, Xiangnan; Shen, Caijun; Liao, Ningbo
A three dimensional model of Multi-Chip Module (MCM) was built with ANSYS based on the internal structure, dimension and material of the MCM produced by Atmel Corporation. The internal and surface temperature distribution of the MCM working in typical mode was studied with the aid of ANSYS. Then heat dissipation proportion of each part of the model and the effect of thermal conductivity on internal temperature of MCM was analysed. The surface temperature of MCM obtained by simulation and the result measured by Thermal Infrared Imager is consistent, so the Finite Element (FE) model and analytical method in this paper can be used to simulate the temperature distribution of MCM quite accurately.